Relationship of social network, social support, religiosity and perceived stress among older adults in Peninsular Malaysia - Abdul Dzahir, Azzida Anom (2018)
Perceived stress is an important indicator of mental and physical health amo ng elderly. Chronic activation from stress perceived by elderly may negatively affect their mental and physical health over time, which subsequently cause increase in the number of elderly seeking medical treatments. Social network, social support and relig iosity may influence elderly’s perceived stress, however there is a dearth of research on perceived stressed among older Malaysians. Thus, this study aims to determine the predictors of perceived stress among older adults in Peninsular Malaysia. A total of 2322 older respondents participated in this study. Instruments used in this study included Perceived Stress Scale-4, Lubben Social Network-6, Medical Outcome Study Social Support Survey, and Religiosity Intrinsic-Extrinsic Scale.